Selectivity of bis(calix[4]diquinone) ionophores towards metal ions in solvent dimethylsulfoxide: a molecular mechanics and molecular dynamics study. - Felix, V; Drew, MG; Webber, P; Beer, P (2006)
Molecular modelling studies have been carried out on two bis(calix[4]diquinone) ionophores, each created from two (calix[4]diquinone)arenes bridged at their bottom rims via alkyl chains (CH(2))(n), 1: n = 3, 2; n = 4, in order to understand the reported selectivity of these ligands towards different sized metal ions such as Na(+), K(+), Rb(+), and Cs(+) in dmso solution. Conformational analyses have been carried out which show that in the lowest energy conformations of the two macrocycles, the individual calix[4]diquinones exhibit a combination of partial cone, 1,3-alternate and cone conformations. The interactions of these alkali metals with the macrocycles have been studied in the gas phase and in a periodic box of solvent dmso by molecular mechanics and molecular dynamics calculations. Molecular mechanics calculations have been carried out on the mode of entry of the ions into the macrocycles and suggest that this is likely to occur from the side of the central cavity, rather than through the main axis of the calix[4]diquinones. There are energy barriers of ca. 19 kcal mol(-1) for this entry path in the gas phase, but in solution no energy barrier is found. Molecular dynamics simulations show that in both 1 and 2, though particularly in the latter macrocycle, one or two solvent molecules are bonded to the metal throughout the course of the simulation, often to the exclusion of one or more of the ether oxygen atoms. By contrast the carbonyl oxygen atoms remain bonded to the metal atoms throughout with bond lengths that remain significantly less than those to the ether oxygen atoms. Free energy perturbation studies have been carried out in dmso and indicate that for 1, the selectivity follows the order Rb(+) approximately K(+) > Cs(+) >> Na(+), which is partially in agreement with the experimental results. The energy differences are small and indeed the ratio between stability constants found for Cs(+) and K(+) complexes is only 0.60, showing that has only a slight preference for K(+). For the larger receptor , which is better suited to metal complexation, the binding affinity follows the pattern Cs(+) >> Rb(+) >> K(+) >> Na(+), with energy differences of 5.75, 2.61, 2.78 kcal mol(-1) which is perfectly consistent with experimental results.